2022
DOI: 10.1093/geronb/gbac105
|View full text |Cite
|
Sign up to set email alerts
|

A Protection Motivation Theory Approach to Understanding How Fear of Falling Affects Physical Activity Determinants in Older Adults

Abstract: Objectives This study applied an extended Protection Motivation Theory to investigate the relative importance of fear of falling (FoF) among motivational and intentional determinants of physical activity (PA) behavior. Methods Older U.S. adults (N = 667, 65+) were surveyed using online research panels and completed measures of self-efficacy and response efficacy (coping appraisal), perceived vulnerability and perceived severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Perceived threats are a behavior level construct that has been shown to be associated with several health behaviors. Specifically, previous work supports the associations between physical activity and perceived threats among older adults [ 41 ]. Other related findings has shown the severity/seriousness component of threat construct to predict intentions to exercise among patients with coronary artery disease [ 42 ].…”
Section: Discussionmentioning
confidence: 53%
“…Perceived threats are a behavior level construct that has been shown to be associated with several health behaviors. Specifically, previous work supports the associations between physical activity and perceived threats among older adults [ 41 ]. Other related findings has shown the severity/seriousness component of threat construct to predict intentions to exercise among patients with coronary artery disease [ 42 ].…”
Section: Discussionmentioning
confidence: 53%
“…Thirdly, female sex, fall history, and compromised sides were related to FOF, while neither hearing nor visual problems were associated with FOF. It was reported that women showed significantly worse FOF conditions than men [57]; this gender difference still applies to older stroke patients. FOF in women over 60 years of age has been associated with factors such as menopause, which may generate a decrease in bone mineral mass and hormones [58].…”
Section: Discussionmentioning
confidence: 95%
“…This finding suggests that fear stimulates protective factors among these older individuals since it has been conceptualised as an affective state defending one against danger and motivating people to practise protective behaviours [ 8 , 15 ]. Conversely, their greater fear could be due to fear of falling or losing their independence once they fall [ 12 ]. In addition, it could also be due to their low self-efficacy, little ability to prevent falls or lack of knowledge in dealing with fall prevention, causing an increase in their fear [ 12 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, their greater fear could be due to fear of falling or losing their independence once they fall [ 12 ]. In addition, it could also be due to their low self-efficacy, little ability to prevent falls or lack of knowledge in dealing with fall prevention, causing an increase in their fear [ 12 , 45 , 46 ]. Therefore, providing continuous fall prevention education and support in their coping appraisal by healthcare providers and family members may reduce their fear.…”
Section: Discussionmentioning
confidence: 99%